Analisis Perbedaan Kualitas Pelayanan Pada Pasien Bpjs Dan Pasien Umum Terhadap Kepuasan Pasien Di Rawat Jalan Rsud Kota Surakarta - Pertiwi, Aisah Ayu Nur, Prof. Dr. Rusdi Lamsudin, Sp.S, Drs. M. Farid Wajdi, MM.,Ph.D (2016)
The purpose of this study was to determine differences in the quality of service based on patient safety, effectiveness and efficiency, and patient centeredness, as well as patient satisfaction between patients using BPJS and General. The study was conducted as many as 60 respondents consisted of 30 patients BPJS and 30 general patients Rawat Jalan Hospital Surakarta. analysis of the data used is the independent t-test and analyzed the influence of the independent variable on the dependent using multiple regression analysis. the study says there are significant differences of quality of service based on patients safety, effective and efficiency, and patient centeredness, as well as patient satisfaction between patients using BPJS and Geeral, as well as the influence of variable patient safety, ffectiveness and efficiency, and patient centeredness to client satisfaction. Forming that the three independent variables are patient safety, effectiveness and efficiency, and patient centeredness have positive effect on customer satisfaction. This means that if patient safety, effectiveness and efficiensi and patient centeredness, the higher patient satisfaction.